New Antihypertensive Agents. II. Studies on New Analogs of 4-Piperidylbenzimidazolinones - TAKAI, HARUKI; SHUTO, KATSUICHI; TERANISHI, MASAYUKI; KUBO, KAZUHIRO; KASUYA, YUTAKA; OBASE, HIROYUKI; NAKAMIZO, NOBUHIRO; SHIGENOBU, KOKI (Chemical & pharmaceutical bulletin, 1982)
As a part of our search for new antihypertensive agents, several 4-piperidylbenzimidazolinone derivatives (I-III) were synthesized. These compounds showed only moderate antihypertensive activity in three hypertensive rat models.